Opportunities and Challenges for SMES for "Green" Management - Vasileva, Elka; Hristova–Pesheva, Yulia; Ivanova, Daniela (Research Papers, 2018)
SMEs are seen as the cause of serious negative environmental impact due to the cumulative effect of their activities, resulting in a general pollution exceeding that of large companies. The transition of SMEs to green management is essential for the reduction of this impact on the environment and for making the use of energy and natural resources efficient. This article aims to explore the opportunities and challenges for SMEs in Bulgaria in relation to green management. The study, directed at micro, small and medium-sized companies in the country, aims through in-depth interviews to reveal their views on green business management and the expectations and challenges related to it. The obtained results allow to outline guidelines for the implementation of green practices as well as topics for future green management training among SMEs. The study's limitations are mainly related to the selection of participants who are representatives of micro, small and medium-sized companies from different sectors of the economy without any claims of representativeness. This does not allow generalization of the conclusions for the whole country as well as for all economic sectors.
Keywords: “Green” management; Business opportunities; Challenges; Micro; Small and medium-sized enterprises; SMEs; Bulgaria